2020
DOI: 10.1111/1365-2656.13242
|View full text |Cite
|
Sign up to set email alerts
|

Increased allocation to reproduction reduces future competitive ability in a burying beetle

Abstract: 1. The existence of a trade-off between current and future reproduction is a fundamental prediction of life history theory. Support for this prediction comes from brood size manipulations, showing that caring for enlarged broods often reduces the parent's future survival or fecundity. However, in many species, individuals must invest in competing for the resources required for future reproduction. Thus, a neglected aspect of this trade-off is that increased allocation to current reproduction may reduce an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 65 publications
2
22
1
Order By: Relevance
“…We also note that we used a relatively small brood size (10 larvae) in our experiment, which suggests that females in all treatments would have had the capacity to increase their level of care in response to a change in the actual age of the larvae. Secondly, there is little evidence that care incurs detectable energetic costs to females in our study species (Richardson, Stephens, & Smiseth, 2020). This is likely to reflect that females provision their larvae with food from a resource that has been acquired prior to breeding (i.e.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We also note that we used a relatively small brood size (10 larvae) in our experiment, which suggests that females in all treatments would have had the capacity to increase their level of care in response to a change in the actual age of the larvae. Secondly, there is little evidence that care incurs detectable energetic costs to females in our study species (Richardson, Stephens, & Smiseth, 2020). This is likely to reflect that females provision their larvae with food from a resource that has been acquired prior to breeding (i.e.…”
Section: Discussionmentioning
confidence: 85%
“…This is likely to reflect that females provision their larvae with food from a resource that has been acquired prior to breeding (i.e. the carcass of a small vertebrate), and that females also feed from carcass and thereby replenish their body reserves during breeding (Richardson et al., 2020). However, we note that such constraints may play an important role in species where parents make repeated foraging trips to the brood, such as in birds.…”
Section: Discussionmentioning
confidence: 99%
“…Females may have a higher optimal body weight than males given that females must secure a carcass to reproduce, which means that they must fly in search of a carcass and compete with rival females. Gaining more weight might be beneficial given that flight is energetically costly and that heavier females tend to win more fights than lighter ones (Richardson et al, 2020). In contrast, males can attract and mate with females away from a carcass by emitting pheromones (Pukowski, 1933) and emitting pheromones is presumably less energetically costly than flying.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on reproductive trade-offs have manipulated traits that affect levels of parental effort to current reproduction (such as brood size or clutch size) and then assessing the induced changes in future survival, life span, or reproductive performance. Some studies have found that increased allocation to current reproduction leads to a future cost, such as lower body condition (Ratz and Smiseth, 2018), lower fecundity (Billman et al, 2014), shorter life span (Daan et al, 1996), or reduced competitive ability over food resources (Richardson et al, 2020), whereas other studies failed to demonstrate the predicted trade-off relationships in future breeding attempts (Roff and Fairbairn, 2007;Santos and Nakagawa, 2012;Ratz et al, 2020). Several explanations have been proposed for whether the trade-off between current and future reproduction are predictable or not.…”
Section: Introductionmentioning
confidence: 99%
“…The carcass serves as the sole source of food for both parents and larvae during breeding (Scott, 1998;Trumbo and Xhihani, 2015;Pilakouta et al, 2016), thus female burying beetles benefit from male desertion by feeding more from the carcass (Boncoraglio and Kilner, 2012). Both parents gain weight during the entire breeding, and the weight gained can serve as a proxy for investment in future reproduction (Creighton et al, 2009;Billman et al, 2014;Pilakouta et al, 2016;Richardson et al, 2020). Likewise, the weight loss during the larvae provisioning is an indicator of the reproductive investment to current reproduction (Trumbo and Xhihani, 2015).…”
Section: Introductionmentioning
confidence: 99%